Effects of yellow seed coat mutation on oil and protein contents in seeds of Brassica napus L - LIU Yu; WANG Fulin; LIU Renhu (浙江大学学报. 农业与生命科学版)
Seed coat colour was one of the most important agronomic traits in Brassica napus L., which was believed to be related with oil content and meal quality. Traditional hypothesis on the relation of seed coat colour with oil content and protein content focused on the reduction of fibre content in the yellow seeds. However in different reports, results on the hypothesis varied. The effects of genetic backgrounds and environments on oil content and protein content were believed to be responsible for the variation.In order to investigate the effects of seed coat colour on oil content and protein content more accurately, the genetic backgrounds and environments need to be kept identical as much as possible for the seeds with different colours.In this study, we isolated a single gene controlled yellow seed coat mutation of B. napus L., on which yellow seeds and brown seeds were seeded in single silique simultaneously. Based on the yellow seeds and brown seeds isolated from the single plants, effects of seed coat colour on oil content and protein content were precisely measured at identical genetic backgrounds and environments. In this research, oil contents of yellow seeds and brown seeds isolated from single plants were measured by Soxhlet lipid extraction method. Protein content was measured by Hitachi L-8900 amino acids analyzer.Results showed that oil contents of yellow seeds and brown seeds isolated from Plant 1 were (49.58±0.26)% and (49.90±0.28)%, respectively. Oil contents of yellow seeds and brown seeds from Plant 2 were (49.65 ± 0.27)% and (49.36±0.25)%, respectively. That from Plant 3 and Plant 4 were (48.68±0.21)% and (48.82±0.17)%, (49.41 ± 0.19)% and (49.46 ± 0.13)%, respectively. The difference was not statistically significant (P=0.87). The yellow seeds and the brown seeds derived from the single plant showed the same oil content. However, the protein content was significantly improved in the yellow seeds. The total hydrolyzed amino acids contents in the yellow seed meal and the brown seed meal were (2 139.48±17.59)μmol/g and (2 063.31±24.53) μmol/g, respectively. The difference was significant (P=0.0194). The most dramatically improved amino acids were tyrosine (9.0% improved) and phenylalanine (8.5% improved) in the yellow seed meal. Aspartate and lysine contents were as well improved 6.5% and 5.2% in the yellow seed meal, respectively. Electron microscopy revealed that the cell wall of inner cell layer of seed coat was decreased in yellow seeds. It was deduced that this may be one of the causes to improve the protein content in yellow seeds. Acidic hydrolysate of seed meal showed that phenylalanine (tyrosine was from phenylalanine) was the most dramatically improved amino acid in the yellow seed meal. Realtime qPCR revealed that the genes encodingβ-D-glucan exohydrolase and phenylalanine ammonia-lyase were related on the yellow seed coat mutation. Transcription of BnaA06g17630D (encoding β-D-glucan exohydrolase) in the brown seed coat was increased by 1.6 folds as compared with the yellow seed coat. Transcription of BnaA05g28470D (encoding phenylalanine ammonia-lyase) in the yellow embryo was increased by 1.8 folds as compared with the brown embryo. We hypothesized that the phenylalanine used for pigment synthesis in the brown seeds was used for protein synthesis in the yellow mutation so that protein content was improved. The amount of protein increase and fibre decrease in yellow seeds might be fair so that oil content was unaffected. It was interesting that lysine content in the brown and yellow oil seed meal was 7.35% and 7.42%, respectively, much higher than that in soybean (5.4%). Thus, it was valuable to be used as lysine additive for grain feed.In conclusion, the yellow seed coat mutation of B. napus was independent with seed oil content but improved protein content significantly. Phenylalanine was the most dramatically improved amino acid in the yellow seed coat mutation. The lysine content was improved as well. The yellow seed meal was valuable to be as lysine additive for grain feed. Transcription of the genes encoding β-D-glucan exohydrolase (BnaA06g17630D) and phenylalanine ammonia-lyase (BnaA05g28470D) were related to yellow seed coat mutation.